Усовершенствованная математическая модель динамики уровня жидкости в барабанном парогенераторе как объекте управления - Климчук, А.А.; Ложечников, В.Ф.; Михайленко, В.С.; Ложечникова, Н.В. (Проблемы управления и информатики, 2019)
В настоящей работе для парогенераторов барабанного типа получена математическая модель, позволяющая повысить точность моделирования переходных процессов в автоматических системах регулирования уровня пароводяной смеси. Розглянуто особливості математичного моделювання динамічних властивостей рівня пароводяної суміші у барабанному парогенераторі. Показано, що вкрай несприятливе для автоматичних систем керування закипання рівня пароводяної суміші у барабанному парогенераторі є наслідком як протікання складних теплофізичних процесів, так і конструктивних особливостей технологічної ділянки. Тому використання для моделювання динаміки рівня математичних моделей, в яких не враховується вплив акумулюючої і дроселюючої властивостей паропроводу на витрату насиченої пари з парогенератора, а головний вплив збурення (витрата пару) розглядається як незалежна змінна, є некоректним. Запропоновано лінійну математичну модель ділянки живлення барабанного парогенератора, яка враховує динамічні властивості паропроводу, що зʼєднує парогенератор із споживачем. Аналіз структурної схеми запропонованої математичної моделі показав, що між барабанним парогенератором і паропроводом існує зворотний взаємозвʼязок витрати пари. Негативний характер звʼязку пояснює самовирівнювання рівня, пов'язане зі зміною положення регулюючого клапана витрати пари або виділенням тепла у котельній камері. Відповідно, зміна площі прохідного перетину регулюючого клапана турбіни, без зміни регулятором теплового навантаження тепловиділення в котельній камері або ядерному реакторі, призводить до тимчасової зміни витрати пари, тобто до менш інтенсивного закипання рівня і його переходу до нового сталого значення. Стабілізація рівня відбувається нижче вихідного значення внаслідок короткочасного порушення балансу між подачею живильної води в парогенератор і відбором пари. Виявлені в результаті рішення системи диференціальних рівнянь особливості поведінки рівня пароводяної суміші дозволяють більш адекватно моделювати роботу існуючих та перспективних систем керування живленням барабанних парогенераторів. The features of mathematical modeling of the dynamic properties of the level of a steam-water mixture in a drum-type steam generator are considered. It is shown that the boiling up of the level of the steam-water mixture in the drum-type steam generator, which is extremely unfavorable for automatic control systems, is a consequence of the occurrence of complex thermophysical processes and the design features of the technological section. Therefore, the use of mathematical models for modeling the level dynamics, which do not take into account the effect of the accumulating and throttling properties of the steam line on the saturated vapor flow from the steam generator, and the main disturbing action (steam consumption) is considered as an independent variable, is not correct. The article proposes a linear mathematical model of the power supply section of the drum steam generator, which takes into account the dynamic properties of the steam line connecting the steam generator with the consumer. Analysis of the structural scheme of the proposed mathematical model showed that between the drum-type steam generator and the steam line there is an inverse relationship with steam consumption. The negative nature of this connection explains the self-leveling associated with a change in the position of the steam flow control valve or heat generation in the combustion chamber. Accordingly, a change in the flow area of the turbine control valve, without changing the heat release by the heat load regulator in the combustion chamber or nuclear reactor, leads to a temporary change in steam consumption. This leads to less intense boiling up of the level and its transition to a new steady-state value. Stabilization of the level occurs below the initial value due to a brief disruption of the balance between the feedwater supply to the steam generator and the extraction of steam. Identified, as a result of solving a system of differential equations, the peculiarities of the behavior of the steam-water mixture level make it possible to simulate more adequately the operation of existing and prospective power management systems for drum-type steam generators.